2015
DOI: 10.1063/1.4928102
|View full text |Cite
|
Sign up to set email alerts
|

Shear-flow trapped-ion-mode interaction revisited. I. Influence of low-frequency zonal flow on ion-temperature-gradient driven turbulence

Abstract: Collisionless trapped ion modes (CTIMs) turbulence exhibits a rich variety of zonal flow physics. The coupling of CTIMs with shear flow driven by the Kelvin-Helmholtz (KH) instability has been investigated. The work explores the parametric excitation of zonal flow modified by wave-particle interactions leading to a new type of resonant low-frequency zonal flow. The KH-CTIM interaction on zonal flow growth and its feedback on turbulence is investigated using semi-Lagrangian gyrokinetic Vlasov simulations based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…This instability is commonly observed in the Earth's clouds, ocean surfaces, atmospheres of Jupiter and Saturn but also in the solar corona [4] and so on. Recently, it has been demonstrated that the KH instability can play an important role also in the zonal flow dynamics of the tokamak devices [5][6][7]. Generally, this instability is presented as a mechanism of saturation able to dissipate the energy related to the velocity shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…This instability is commonly observed in the Earth's clouds, ocean surfaces, atmospheres of Jupiter and Saturn but also in the solar corona [4] and so on. Recently, it has been demonstrated that the KH instability can play an important role also in the zonal flow dynamics of the tokamak devices [5][6][7]. Generally, this instability is presented as a mechanism of saturation able to dissipate the energy related to the velocity shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…Since the model has been already derived in a previous work [27], we just recall here the main features relevant to the ZF dynamics. Assuming that dn 0 dψ is zero, in order to simplify the treatment, we just consider an ITG instability driven only by an initial temperature gradient, which corresponds to suppressing the second term dn 0 dψ ψ ∂φ ∂ψ ∂φ ∂α α dψ in (24).…”
Section: The Kinetic Nature Of Zf Driven By Timmentioning
confidence: 99%
“…From the work described in Ref. [27], the answer appears to lie in the fact that the nature of the ZF is strongly modified by nonlinear effects induced by the resonant character of (kinetic) TIMs, at least for the case of turbulence met in tokamaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While substantial effort has been devoted to the study of ZF generation by drift-wave or Ion Temperature Gradip-1 ent (ITG) modes, little work has been published on zonal flows driven by pure collisionless trapped ion modes or by their electron counterpart, the collisionless trapped electron modes (CTEMs) when electron dynamics is taken into account. Recently in Refs [11,12], we have identified a nonlinear coupling mechanism of ZF mediated by CTIMs in the collisionless regime, leading to a non-zero low-frequency ZF mode of resonant nature (with the possibility to an amplification by wave-"banana" resonance). While zero-frequency ZFs are quite non resonant, being relativily easy to drive up by the Reynolds tensor, this new low-frequency oscillating component of ZF becomes sensible to a strong amplification induced by the resonant interaction between CTIM and CTEM.…”
mentioning
confidence: 99%